2020
DOI: 10.1126/sciadv.aaz3152
|View full text |Cite
|
Sign up to set email alerts
|

The insulator functions of theDrosophilapolydactyl C2H2 zinc finger protein CTCF: Necessity versus sufficiency

Abstract: In mammals, a C2H2 zinc finger (C2H2) protein, CTCF, acts as the master regulator of chromosomal architecture and of the expression of Hox gene clusters. Like mammalian CTCF, the Drosophila homolog, dCTCF, localizes to boundaries in the bithorax complex (BX-C). Here, we have determined the minimal requirements for the assembly of a functional boundary by dCTCF and two other C2H2 zinc finger proteins, Pita and Su(Hw). Although binding sites for these proteins are essential for the insulator activity of BX-C bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 41 publications
2
30
0
5
Order By: Relevance
“…3g). These results suggest that, depending on the locus, CTCF may directly repress or activate the transcription of nearby genes, or alternatively CTCF may shield promoters from inappropriate enhancers or silencers as observed at Hox gene loci 21,40 .…”
Section: Ctcf Impacts Expression Patterns Of Genes Near Ctcf Peaksmentioning
confidence: 81%
See 1 more Smart Citation
“…3g). These results suggest that, depending on the locus, CTCF may directly repress or activate the transcription of nearby genes, or alternatively CTCF may shield promoters from inappropriate enhancers or silencers as observed at Hox gene loci 21,40 .…”
Section: Ctcf Impacts Expression Patterns Of Genes Near Ctcf Peaksmentioning
confidence: 81%
“…CTCF occupancy scales with enhancer-blocker activity in a reporter assay. Previous studies of the functionality of CTCF binding sites stably integrated into the fly genome suggested that most of them lack insulator activity (i.e., the ability to block regulatory crosstalk) 36 , at least in single copies 40 . Here, we tested CTCF peaks in a quantitative reporter assay.…”
Section: Ctcf Impacts Expression Patterns Of Genes Near Ctcf Peaksmentioning
confidence: 99%
“…The Mcp boundary contains binding sites for dCTCF and Pita [ 145 ]. The Fub boundary contains binding sites for CTCF, Su(Hw), and Pita [ 145 , 146 , 147 ]. Similar to dCTCF, Su(Hw) and Pita have clusters of C2H2 domains, some of which facilitate the specific binding of these proteins with DNA motifs [ 148 , 149 , 150 ].…”
Section: Super-long-distance Interactions In the Drosophmentioning
confidence: 99%
“…The Zw5 protein was originally identified as a key factor of the scs insulator at the boundary of the hsp70 cluster ( 18 , 19 ) and can effectively support long-range interaction between its binding sites ( 20 ). The Pita protein functions in cooperation with dCTCF and Su(Hw) in organization of insulator/boundary elements in the bithorax complex ( 21 , 22 ). In transgenic lines, the ZAF1 protein can form a chromatin loop that isolates the eye enhancer from the white gene ( 13 ).…”
Section: Introductionmentioning
confidence: 99%